ANALISIS NILAI TAMBAH KRIPIK DAUN JAMBU BIJI MERAH (JASEP, 2017)
The purpose of this study was to determine how the red guava agribusiness in Air Kumbang Bakti Village, District Air Kumbang, Banyu Asin Regency, Province of South Sumatra; to find out how the development prospects of red guava agribusiness in Air Kumbang Bakti Village, District Air Kumbang, Banyu Asin Regency, Province of South Sumatra; and to know how big is the value added of the red guava leaves chips processing in Air Kumbang Bakti Village, District Air Kumbang, Banyu Asin Regency, Province of South Sumatra. This research has been conducted in Air Kumbang Bakti Village, District Air Kumbang, BanyuAsin Regency, Province of South Sumatra. The election of this village as the location was done intentionally (purposive). With considerations that in this area, there are few farmers who growth red guava and also proceed the guava leavess as a chips. Implementation of field research was conducted from March to June 2016. Methods study is a survey method. The sampling method used in this study were randomly (simple random sampling).The samples taken is 1 person from 10 populations. From the research results can be concluded as follows: 1). The Red guava agribusiness production starting from land preparation, cultivation and marketing of guava, 2). Farmers guava can enjoy the red guava trade economic improvement through diversification from guava, such as red guava leaves chips, because the value-added from processing chips red guava leaves can provide contribution amounting to 75.00 per cent for the income of farmers guava.